Electrons and disorder in solids - Gantmakher, V. F.; Oxford eBooks (Oxford : Clarendon, 2005)
Written for those studying solid state physics, this work contains modern concepts about the physics of electrons in solids. The emphasis is laid on various physical models aimed at stimulating creative thinking.
Translated from the Russian.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Free electron theory of metals; Electrons -- Scattering; Electron transport; Order-disorder models; Solid state physics; Electron configuration; Electronic books